Meat intake and risk of inflammatory bowel disease: A meta-analysis - Ge, Jian; Han, Tian-Jie; Liu, Jin; Li, Jun-Shan; Zhang, Xiao-Hua; Wang, Yu; Li, Qing-Yan; Zhu, Qiang; Yang, Chong-Mei (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: This meta-analysis is designed to determine the association between meat consumption and the risk of inflammatory bowel disease. Materials and Methods: Search relevant literature published in PubMed, Cochrane before July 2015 without restrictions. Studies were included if relative ratios and the corresponding 95% confidence intervals of the risk of inflammatory bowel disease were reported with respect to meat consumption. Results: Nine studies were included in this meta-analysis. Relative to those who did not or seldom eat meat, meat consumers had a significantly greater risk of inflammatory bowel disease (pooled relative ratio: 1.50, 95% confidence interval: 1.15–1.95). The funnel plot revealed no evidence for publication bias. Conclusion: Meat consumption may increase the risk of inflammatory bowel disease. Additional large prospective studies are warranted to verify this association.